The role and importance of organizational principles in olympic education - Mamajonov, Dilshodbek; Yuldashev, Rashid (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article examines the principles of advocacy and their importance in the organization of Olympic education, and provides conclusions and practical recommendations. Olympic education, with its educational features, requires specific organizational principles and plays a special role in the organization of this educational process